ON DIGITAL ETHNOGRAPHY: NONVIOLENT CAMPAIGN MOVEMENT OF THE INSTAGRAM COMMUNITY @TOLERANSI.ID IN REALIZING RELIGIOUS MODERATION - Pamungkas, Martinus Danang; Suleman, Zulfikri; Santoso, Anang Dwi (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This study discusses the movements of the Instagram community @toleransi.id in promoting religious moderation through nonviolent campaigns during online radicalism and religious extremism. Instagram is used as a tool to achieve religious harmony. However, the community faces challenges such as digital repression and restrictions on the freedom of religious expression. The research method involves qualitative descriptive content analysis. Furthermore, digital ethnography is used to holistically understand the cultural and social experiences of @toleransi.id community activities in the digital world of Instagram. Data were collected through observation and documentation of digital content published by @toleransi.id from 2019 to 2023. Data analysis involved symbol classification, determination of analysis criteria, and analysis using the theoretical and conceptual frameworks of nonviolent campaigns, networked social movements, and religious moderation. The results show that this community faces semantic and behavioral barriers due to the open autonomy space of the internet. They use tactics such as creative and inclusive digital content, dialogue spaces, intellectual discourse, and Instagram as a campaign platform to influence public opinion and build networks. The findings contribute to the study of social movements and religious moderation by showing how @toleransi.id initiated a religious moderation movement with a nonviolent campaign initiated by the Internet autonomy space